The road is good : how a mother's strength became a daughter's purpose - Aduba, Uzo (Viking, 2024)
"The Road Is Good is a memoir of Black immigrant identity, the coming-of-age story of Nigerian American actress Uzo Aduba, one of the stars of the television series Orange is the New Black"--